The Determinants of Indonesia's Coal Exports Demand to Six Asian Countries - Susanto, Deni Aditya; Admi, Randy (Journal of Developing Economies, 2021)
Coal is one of the most needed commodities globally because of its power plants and industrial machinery. According to World Coal Institute (2018), the world coal trade is dominated by several producing countries, Indonesia (ranked 2nd with 28.21 percent). Indonesia's coal exports are influenced by determinants of demand from export destination countries. This study will test at least four demand determinants in destination countries for their effects on Indonesian exports: exchange rate, foreign exchange reserves, population, and coal production. The study used six Asian countries (Japan, South Korea, India, Thailand, Philippines, and Malaysia) over 2008-2018. The methodology used is multiple linear regression with a series of chow and Hausman tests. Each variable has been tested by t-test (partial) and f test (simultaneous), and R2 test to analyze the percentage of the influence of the model on the dependent variable. This study revealed that the variable foreign exchange reserves and population growth of six Asian countries have a significant positive effect on Indonesia's coal export. Simultaneously, the exchange rate and coal production of the destination countries were not proven to have a negative impact but positively affected coal export. All variables have a significant and partially significant effect so that the model can explain the coal export variable at 93.08 percent (Adjust R-squared). Keywords: Coal Export, Demand Determinants JEL: C2, F1, Q31